A Novel Proposal for an Index for Regional Cerebral Perfusion Pressure – A Theoretical Approach Using Fluid Dynamics - Kameyama, Masashi; Momose, Toshimitsu; Ishibashi, Kenji; Ishii, Kenji (Frontiers in Neurology, 2022)
Cerebral blood flow (CBF) / cerebral blood volume (CBV) ratio derived by [15O] H2O/ CO2 and CO positron emission tomography (PET) examination has been used as an index for cerebral perfusion pressure (CPP). CBF/CBV was demonstrated to be related mean arterial pressure (MAP) in baboons. However, this formula has not been confirmed to be proportionate to CPP. We have developed a new index for CPP using the Poiseuille equation based on a simple model. Our model suggests that CBF/CBV2 is proportionate to CPP and that it is mathematically a more accurate index than CBF/CBV. This new index needs experimental validation in the future.